2018
DOI: 10.3389/fimmu.2018.02438
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Circulating CD4+Ki67+HLA-DR− T Regulatory Cells Prior to Treatment for Multidrug Resistant Tuberculosis Can Differentiate the Severity of Disease and Predict Time to Culture Conversion

Abstract: Identifying a blood circulating cellular biomarker that can be used to assess severity of disease and predict the time to culture conversion (TCC) in patients with multidrug resistant tuberculosis (MDR-TB) would facilitate monitoring response to treatment and may be of value in the design of future drug trials. We report on the frequency of blood Ki67+HLA-DR− CD4+ T regulatory (Treg) cells in predicting microbiological outcome before initiating second-line treatment for MDR-TB. Fifty-one patients with MDR-TB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
3
9
1
Order By: Relevance
“…As we expected, the CD4 + CD27 − T-cell subset was the predominantly activated population for all stimulation conditions, as demonstrated through HLA-DR, CD38, IFN-γ, and TNF-α expression levels, which is consistent with previous studies (18,21). CD4 + T-cells are important in controlling Mtb infection and those that are CD27 − are mostly TEMRA, EM, and effector cells which exert the quickest and strongest activated effector response (18,26). However, this subset is also the most likely to undergo activation induced cell death and to be exhausted from persistent antigen stimulation in vivo which will reduce their frequency (27).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As we expected, the CD4 + CD27 − T-cell subset was the predominantly activated population for all stimulation conditions, as demonstrated through HLA-DR, CD38, IFN-γ, and TNF-α expression levels, which is consistent with previous studies (18,21). CD4 + T-cells are important in controlling Mtb infection and those that are CD27 − are mostly TEMRA, EM, and effector cells which exert the quickest and strongest activated effector response (18,26). However, this subset is also the most likely to undergo activation induced cell death and to be exhausted from persistent antigen stimulation in vivo which will reduce their frequency (27).…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, CD27 is expressed on central memory (CM) T-cells, variably expressed on effector memory (EM) T-cells and is not expressed on terminal effector memory (TEMRA) T-cells ( 22 25 ). As we expected, the CD4 + CD27 – T-cell subset was the predominantly activated population for all stimulation conditions, as demonstrated through HLA-DR, CD38, IFN-γ, and TNF-α expression levels, which is consistent with previous studies ( 18 , 21 ). CD4 + T-cells are important in controlling Mtb infection and those that are CD27 – are mostly TEMRA, EM, and effector cells which exert the quickest and strongest activated effector response ( 18 , 26 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to animal model studies, where changes in circulating T reg frequency can impact infection levels, reports of T reg frequencies in human TB are varied. Some studies show an increase in peripheral T reg frequencies in TB [75–78]. However, our study [64] and others [79,80] found no differences in peripheral T reg frequencies between pulmonary TB patients and healthy controls.…”
Section: Tuberculosiscontrasting
confidence: 86%
“…While IL-4 has been implicated in the development [52] and maintenance of Tregs [53], the data are conflicting and this relationship has never been demonstrated in the context of human TB. There is substantial evidence on the detrimental role of Tregs in drugsensitive TB [25,[54][55][56], drug-resistant TB [26,57], and TB/HIV co-infection [58], including attenuation of mycobacterial containment in vitro [25,26], and downregulating Th1 responses [25,56]. There is substantial evidence on the detrimental role of Tregs in TB [25,26,56] including attenuation of mycobacterial containment in vitro [25,26], and downregulating Th1 responses [25,56].…”
Section: Discussionmentioning
confidence: 99%